2014
DOI: 10.1017/etds.2013.96
|View full text |Cite
|
Sign up to set email alerts
|

On rationally ergodic and rationally weakly mixing rank-one transformations

Abstract: Abstract. We study the notions of weak rational ergodicity and rational weak mixing as defined by Jon Aaronson. We prove that various families of infinite measure-preserving rank-one transformations possess (or do not posses) these properties, and consider their relation to other notions of mixing in infinite measure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…For t > 1/2, T × T is not is not conservative. By [12], rational weak mixing implies weak doubly ergodic, so this give another example of a double ergodic transformation with nonconservative cartesian square. Our examples below can also be chosen to be rigid (Theorem 6.5).…”
Section: A Strictly Weak Doubly Ergodic Rigidity-free Transformation Tmentioning
confidence: 94%
See 2 more Smart Citations
“…For t > 1/2, T × T is not is not conservative. By [12], rational weak mixing implies weak doubly ergodic, so this give another example of a double ergodic transformation with nonconservative cartesian square. Our examples below can also be chosen to be rigid (Theorem 6.5).…”
Section: A Strictly Weak Doubly Ergodic Rigidity-free Transformation Tmentioning
confidence: 94%
“…Now suppose that p > 1. By (12), |I p | < 4qhn−1 jp−ip . Also, for any z ∈ Z with −i p ≤ z < r n − j p , we may write…”
Section: Invariant Sets When T Is Not Wdementioning
confidence: 95%
See 1 more Smart Citation
“…For the genericity result, rather than working with the cutting and stacking construction definition of rank-one transformations (used in examples and in e.g. [11]), we work with the abstract definition of rank-one. As Aaronson [4, §10] has shown that the class of weakly rationally ergodic transformations is meager in the group of measurepreserving transformations, a consequence of our results is that there exist rank-one transformations that are subsequence boundedly rationally ergodic but not weakly rationally ergodic.…”
Section: Preliminariesmentioning
confidence: 99%
“…The methods that we use are combinatorial and probabilistic in nature. Propositions 2.3 and 2.4 use the notion of descendants, as introduced in [8], to turn the dynamics of the rank-one system into combinatorial characterizations.…”
Section: Introductionmentioning
confidence: 99%